1993
DOI: 10.1017/s000748530004181x
|View full text |Cite
|
Sign up to set email alerts
|

The biology and host specificity of Pareuchaetes aurata aurata (Lepidoptera: Arctiidae), a ‘new association’ biological control agent for Chromolaena odorata (Compositae)

Abstract: Pareuchaetes aurata aurata (Butler) from Chromolaena jujuensis in northern Argentina was tested as a biological control candidate for the composite weed C. odorata. The larvae feed voraciously and complete their development on C. odorata. The host-plant feeding range of P. a. aurata is limited to the genus Chromolaena. It is suggested that the egg-laying behaviour of P. a. aurata, which scatters its eggs around the base of the host-plant, will help to overcome the problem of ant predation which prevented the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
3
4
1
Order By: Relevance
“…Our findings indicate that over 74 % of the eggs were laid during the first four nights (after mating) with peak egg laying on the second night. This concurs with the findings of Kluge & Caldwell (1993b) who reported that 70 % of oviposition occurred within the first four nights for P. aurata aurata. This relatively short window exemplifies why protogyny could lead to matelessness.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings indicate that over 74 % of the eggs were laid during the first four nights (after mating) with peak egg laying on the second night. This concurs with the findings of Kluge & Caldwell (1993b) who reported that 70 % of oviposition occurred within the first four nights for P. aurata aurata. This relatively short window exemplifies why protogyny could lead to matelessness.…”
Section: Discussionsupporting
confidence: 93%
“…Mean lifetime fecundity (387 ± 19.62 eggs) per female was 23 % higher than that recorded for a closely related species, P. aurata aurata, where lifetime fecundity averaged 241.9 eggs per female (Kluge & Caldwell 1993b). Our findings indicate that over 74 % of the eggs were laid during the first four nights (after mating) with peak egg laying on the second night.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations